Continuity and/or Discontinuity at Vatican II? Examining the Council in the Context of the ‘Long Nineteenth Century’ - Colberg, Kristin (Heythrop journal, 2012)
This article explores recent questions regarding the interpretation of Vatican II by examining the council's theological and historical relation to what John O'Malley has called ‘the long nineteenth century’. This period, which O'Malley dates from the French Revolution until the end of the pontificate of Pius XII (1958), connotes a time when political and philosophical developments ‘traumatized’ the Church. This sustained trauma left the Church in a defensive position which deeply informed its view of itself and its relation to the world. While a great deal of attention has been directed at examining the council's degree of continuity or discontinuity with the conciliar tradition, not enough has been done to understand its relationship to developments within this more immediate setting. This study argues that a more contextualized appreciation of the Church's efforts to respond to the challenges of the long nineteenth century, expressed especially in the teachings of Vatican I, can illumine key elements of the meaning of Vatican II's documents and the continuity and/or discontinuity that they represent.